Answer:
The expressions are not equivalent because -3(2)(5-4)+3(2-6)=-18 and -12(2)-6=-30
Step-by-step explanation:
Two expressions are said to be equal if after a number is substituted to the expression, they produce the same result (that is they have the same value).
To determine whether -3x(5-4)+3(x-6) is equivalent to -12x-6, we have to substitute the same number to the expression and see if it produces the same result.
Substituting 2 to the first expression gives:
-3×2(5-4) + 3(2 - 6) = -6 - 12 = -18
Substituting 2 to the second expression gives:
-12(2) - 6 = -24 - 6 = -30
Since -3×2(5-4) + 3(2 - 6) = -6 - 12 = -18 and -12(2) - 6 = -24 - 6 = -30, the expressions are not equivalent because they do not produce the same result.
Answer:
1. A particular order in which related events, movements, or things follow each other.
2. A term
3. Patterns offer visual clues to an underlying order. Patterns can also be used as a template that will enable one to quickly analyze a situation and understand how it works.
4. Sequence of numbers such that the difference between the consecutive terms is constant.
If you mean h(4)
h(4)=(4)*2 -5(4)
=8-20
=-12
The answer will be-12
Answer:
24.52
Step-by-step explanation: